Callispheres drug-eluting bead transhepatic artery chemoembolization with oral delivery of sorafenib for the treatment of unresectable liver cancer - Wang, Wenhui; Li, Fenqiang; Gan, Peiying; Li, Baohua; Li, Shuangxi (Frontiers in Surgery, 2022)
Objective: Liver cancer is a significant contributor to global burden of cancer. Transcatheter arterial chemoembolization (TACE) is the standard of care for patients with unresectable liver cancer, and CalliSpheres, as novel drug-eluting bead (DEB) microspheres, have been found to be associated with a high tumor response rate. However, the outcomes after DEB-TACE treatment are not always satisfactory with tumor recurrence. Herein, we attempt to compare the clinical efficacy and safety of DEB-TACE with sorafenib and conventional TACE in treating advanced liver cancer. Methods: The study retrospectively reviewed clinical records of 96 patients with liver cancer, among which there were 48 cases receiving DEB-TACE with sorafenib and 48 cases receiving conventional TACE. The physical properties of Callispheres were evaluated in HepG2 cells and a B6/J mouse model. Results: DEB-TACE with Callispheres were demonstrated to effectively maintain stability and prolong the half-life of epirubicin. Compared with the patients receiving conventional TACE, those receiving DEB-TACE with sorafenib exhibited better patient outcomes with increased survival rate, reduced tumor volume, and declined levels of tumor markers. Additionally, DEB-TACE with Callispheres could effectively protect liver function, as well as reduce the toxic effects of loaded epirubicin, and its combination with sorafenib would not increase the incidence of adverse reactions. Conclusion: DEB-TACE using CalliSpheres combined with sorafenib could prevent the progression of liver cancer and bring a better prognosis.